Recruitment and apprenticeship training - Jens Mohrenweiser (Industrielle Beziehungen, 2016)
The paper assesses non-training firm's potential for free-riding on the training efforts of firms that train apprentices. In order to assess potential free-riding, the paper analyses whether training or non-training firms are more likely to recruit apprenticeship graduates that have been trained elsewhere. Firms without apprentices are less likely to hire apprenticeship graduates trained elsewhere than training firms. If these firms do hire apprenticeship graduates, they hire a smaller proportion compared to all new-hired skilled workers who have an apprenticeship degree than training firms. The paper discusses three potential explanations for this finding: lower demand for apprenticeship graduates, information disadvantage and apprentices' preferences.
Keywords: J24; M51; M53; 330; company-sponsored training; training participation; recruiting; apprenticeship; employer coordination